1985
DOI: 10.2172/5047113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the solid, airborne materials created when UF/sub 6/ reacts with moist air flowing in single-pass mode

Abstract: A series of experiments has been performed in which UF6 was released into flowing air in order to characterize the solid particulate material produced under non-static conditions. In two of the experiments, the aerosol was allowed to stagnate in, a static chamber after release and examined further but in the other experiments characterization was done only on material collected a few seconds after release. Transmission electron microscopy and mass measurement by cascaded impactor were used to characterize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…4 In that work, researchers found only UO 2 F 2 product for UF 6 these two values and no reaction mechanisms were proposed. Additionally, several groups have studied the particle morphology [5][6][7][8][9][10] and reactor design for the production of particles from aerosols of UF 6 . 11…”
Section: Uf 6 + H 2 O → Uof 4 + 2hfmentioning
confidence: 99%
“…4 In that work, researchers found only UO 2 F 2 product for UF 6 these two values and no reaction mechanisms were proposed. Additionally, several groups have studied the particle morphology [5][6][7][8][9][10] and reactor design for the production of particles from aerosols of UF 6 . 11…”
Section: Uf 6 + H 2 O → Uof 4 + 2hfmentioning
confidence: 99%
“…The white fog is an aerosol consisting of particulate matter or particles of complicated chemical composition. After extensive characterization efforts for the particulate materials in the past few decades, we now know that the aerosol population consists of UO2F2 as a main reaction product when UF6 is in contact with H2O vapor (Kessie 1967, Bostick et al 1983, 1984, Kips et al 2007, Kips and Kristo 2009, Pickrell 1982, 1984, 1985. UF6 hydrolysis produces solid UO2F2 particles and also HF, a hazardous toxic gas, as written in Eq.…”
Section: Pathways To Airborne Uranyl Particlesmentioning
confidence: 99%
“…Previous microscopic studies of UO2F2 formation produced many micrographs (Bostick et al 1983, 1984, Kips et al 2007, Pickrell 1982, 1984, 1985. As the UO2F2 particles were produced, they were likely to be in a spherical shape at the beginning.…”
Section: Size Of Primary Particlementioning
confidence: 99%
“…Pickrell investigated morphologies of hydrolyzed UF 6 following gravimetric deposition onto Formarcoated electron microscope grids made of nickel [11][12][13]. A glass or metal sample holder with UF 6 was pressurized with heat, allowing the UF 6 to be released as a liquid.…”
Section: *Manuscriptmentioning
confidence: 99%
“…As observed in Experiment 1, no differences in morphology or particle load were observed between samples collected at 1 cm versus 6 cm from the air inlet. SEM-EDS spectra indicated that the major elemental constituents were uranium, oxygen and fluorine (Supporting Information Figure S In contrast, Pickrell observed formation of ~ 10 μm agglomerates made of discrete spheroids on the order of 0.1 μm in diameter following release of liquid UF 6 to excess water, and suggested that agglomeration of particles over time was likely due to charging [11,12]. Kips reported an increase in the average particle diameter with increased relative humidity [15].…”
Section: Hydrolysis Products Deposited Onto a Carbon Conductive Tapementioning
confidence: 99%